2016
DOI: 10.3390/mi7040052
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Use of Compact Disc-Based Centrifugal Microfluidics for Healthcare Diagnostics at the Extreme Point of Care

Abstract: Since its inception, Compact Disc (CD)-based centrifugal microfluidic technology has drawn a great deal of interest within research communities due to its potential use in biomedical applications. The technology has been referred to by different names, including compact-disc microfluidics, lab-on-a-disk, lab-on-a-CD and bio-disk. This paper critically reviews the state-of-the-art in CD-based centrifugal microfluidics devices and attempts to identify the challenges that, if solved, would enable their use in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 90 publications
1
23
0
Order By: Relevance
“…A notable subset of the microfluidic system types is centrifugal, or lab-on-a-disc, devices, first developed in the late 1990s [24]. The simplicity of operation, the lack of complicated external instrumentation for sample transport (e.g., pumps), the ability to easily eliminate bubbles, and the inherent capability of density-based separation make centrifugal systems uniquely suited for diagnostics at the extreme point-of-care [25,26]. Using basic rotary control, simple microfluidic features can provide a multitude of unit operations, such as valving, metering, and mixing, making it easy to achieve scalable parallelization and integration for an array of samples [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A notable subset of the microfluidic system types is centrifugal, or lab-on-a-disc, devices, first developed in the late 1990s [24]. The simplicity of operation, the lack of complicated external instrumentation for sample transport (e.g., pumps), the ability to easily eliminate bubbles, and the inherent capability of density-based separation make centrifugal systems uniquely suited for diagnostics at the extreme point-of-care [25,26]. Using basic rotary control, simple microfluidic features can provide a multitude of unit operations, such as valving, metering, and mixing, making it easy to achieve scalable parallelization and integration for an array of samples [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the possibility of being able to modify the exposed metal layer using readily available office printers [7,10,76] or similar techniques [73] or chemically to form self-assemble monolayers [32] of for the addition for functional groups [33]. Beyond the scope of this review, reports have shown the possibility of utilising CDs and DVDs for both sample preparation as well as quantification using approaches such as surface plasma resonance [89], centrifugal microfluidics or so called 'lab-on-a-disc' devices [90][91][92][93][94][95], DNA microarrays [96]. Their application in the exploitation of solar energy [97] and the development of batteries [98] has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed an automated-image-analysis smartphone application using machine learning to make assay readout more user-friendly,robust, and free of potential user bias.A tt he current stage,m ultiple hands-on steps are still needed to carry out the incubation and washing steps in microbubbling assays.F urther integration with automated systems,such as autonomous capillary microfluidic systems [31] disk-like microfluidic systems, [32] and programmable electrowetting-based droplet-mixing systems, [33] would simplify the microbubbling assay,m aking it ready for POC applications. We have developed an automated-image-analysis smartphone application using machine learning to make assay readout more user-friendly,robust, and free of potential user bias.A tt he current stage,m ultiple hands-on steps are still needed to carry out the incubation and washing steps in microbubbling assays.F urther integration with automated systems,such as autonomous capillary microfluidic systems [31] disk-like microfluidic systems, [32] and programmable electrowetting-based droplet-mixing systems, [33] would simplify the microbubbling assay,m aking it ready for POC applications.…”
Section: Forschungsartikelmentioning
confidence: 99%